Development of Snake Ladder Game as a Health Promotion Medium for School Aged Children in Pamulang Barat Elemntary School - Happy Novriyanti Purwadi; Aulia Minati; Resna A Soerawidjaja (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
The purpose of this study was to determine the feasibility of health promotion media for snake and dental health ladder games for school-age children in Pamulang Barat Elementary School in 2019. The research method used isResearch and Development method which uses 45 samples of third grade students in Pamulang Barat Elementary School with the distribution of 10 students in the first try and 35 students in the field trials. The results of this study areresults of the assessment of 2 material experts obtained an average score of 42 or 84%. The results of the assessment of 2 media experts obtained an average score of 73 or 73%. The results of the assessment of responses from students in small group trials the average score is 51.3 with an assessment percentage of 98%. The average score of response assessment of 35 students in a large group is 52.8 with 96% assessment percentage. This research shows that the game of snakes and ladders for oral health is categorized as "Worthy" assessed from the media aspect by media experts and learning aspects by material experts. Student responses to the snake and tooth health mouth ladder game can be categorized as "Very Good".